Association of fluid balance with mortality in sepsis is modified by admission hemoglobin levels: A large database study. - Sandra M Y Tan (Public Library of Science (PLoS), 2021)
Purpose Sepsis involves a dysregulated inflammatory response to infection that leads to organ dysfunction. Early fluid resuscitation has been advocated by the Surviving Sepsis Campaign guidelines. However, recent studies have shown that a positive fluid balance is associated with increased mortality in septic patients. We investigated if haemoglobin levels on admission to the intensive care unit (ICU) could modify the association of fluid balance with mortality in patients with sepsis. We hypothesized that with increasing fluid balance, patients with moderate anemia (hemoglobin 7-10g/dL) would have poorer outcomes compared to those without moderate anemia (hemoglobin >10g/dL). Materials and methods This retrospective study utilized the Medical Information Mart for Intensive Care-III (MIMIC-III) database. Patients with sepsis, as identified by the International Classification of Diseases, 9th, Clinical Modification codes, were studied. Patients were stratified into those with and without moderate anemia at ICU admission. We investigated the influence of fluid balance measured within 24 hours of ICU admission on 28-day mortality for both patient groups using multivariable logistic regression models. Subgroup and sensitivity analyses were conducted. Results 8,132 patients (median age 68.6 years, interquartile range 55.1-79.8 years; 52.8% female) were included. Increasing fluid balance (in L) was associated with a significantly decreased risk of 28-day mortality in patients without moderate anemia (OR 0.91, 95%CI 0.84-0.97, p = 0.005, at 6-hour). Conversely, increasing fluid balance was associated with a significantly increased risk of 28-day mortality in patients with moderate anemia (OR 1.05, 95% CI 1.01-1.1, p = 0.022, at 24-hour). Interaction analyses showed that mortality was highest when haemoglobin decreased in patients with moderate anemia who had the most positive fluid balance. Multiple subgroups and sensitivity analyses yielded consistent results. Conclusions In septic patients admitted to ICU, admission hemoglobin levels modified the association between fluid balance and mortality and are an important consideration for future fluid therapy trials.